2013
DOI: 10.3390/v5041055
|View full text |Cite
|
Sign up to set email alerts
|

Early Events in Foamy Virus—Host Interaction and Intracellular Trafficking

Abstract: Here we review viral and cellular requirements for entry and intracellular trafficking of foamy viruses (FVs) resulting in integration of viral sequences into the host cell genome. The virus encoded glycoprotein harbors all essential viral determinants, which are involved in absorption to the host membrane and triggering the uptake of virus particles. However, only recently light was shed on some details of FV’s interaction with its host cell receptor(s). Latest studies indicate glycosaminoglycans of cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 89 publications
1
12
0
1
Order By: Relevance
“…SFV uses heparin sulfate to attach to target cells (47,48), but the receptor for SFV is still unknown (64). Interference studies showed that one cellular receptor is used by all SFVs (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…SFV uses heparin sulfate to attach to target cells (47,48), but the receptor for SFV is still unknown (64). Interference studies showed that one cellular receptor is used by all SFVs (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Gag proteins are central to the assembly of all retroviruses. Their expression in appropriate cells is sufficient to generate extracellular VLPs (with the exception of foamy virus, the assembly and budding of which rely on the envelope glycoproteins) (4,29). To determine the targeting sites of the EIAV and HIV-1 Gag proteins, 293T cells were transfected with EIAV or HIV-1 Gag-GFP plasmids.…”
Section: Eiav Gag Accumulates In Internal Cellular Compartmentsmentioning
confidence: 99%
“…For example, there is no release of a free protease moiety but instead protease activation is mediated by binding to the defined genomic RNA sequence protease-activating RNA motif (PARM) and subsequent dimerization of the Pol polyproteins. For an introduction into the topic, see [20,21,22]. …”
Section: Summary Of Scientific Sessionsmentioning
confidence: 99%
“…FV replication is inhibited by IFN-α, -β, and -γ. Two possible escape mechanisms from the antiviral action of IFNs have been described for FVs: the low lysine content of the Gag protein conferring partial resistance to IFN-α in primary cells and the synthesis of an miRNA inhibiting response to IFN [27]; (3) most steps of the FV life cycle are sensitive to the action of major IFN-induced restriction factors, including the alpha isoform of tripartite motif-containing protein 5 (TRIM5α), apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like (APOBEC), interferon-induced 35 kDa protein (IFP35), TRIM19, and Tetherin [20,31]; (4) regarding the adaptive immune effectors, FV-virus specific T lymphocytes have not been described thus far. Neutralizing antibodies against cell-free FV are detected in most animal and human hosts.…”
Section: Summary Of Scientific Sessionsmentioning
confidence: 99%